Ni3S2 / VN-C / C difunctional electro-catalytic material as well as preparation method and application thereof
By growing the nanostructures of Ni3S2 and VN on the carbon/carbon conductive matrix, the formation of Ni3S2/VN-C/C dual-function electrocatalytic materials is solved, and the water decomposition performance and electrocatalytic efficiency are significantly improved.
Patent Information
- Application Number
- CN202411571441.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing electrocatalysts have limited stability after long-term use and do not perform well under different pH values and temperature conditions, resulting in poor water decomposition performance.
Using Ni3S2/VN-C/C dual-function electrocatalytic material, nanotube-shaped Ni/Ni3S2 and nanoparticle-shaped VN were grown on the carbon/carbon conductive matrix by hydrothermal and sintering to form a heterogeneous interface to improve catalytic activity.
In a strong alkaline environment, the efficiency of electrocatalytic hydrogen evolution and oxygen evolution is significantly improved, and the overpotential is reduced. The overpotential required for electrocatalytic hydrogen evolution is 165mV, the overpotential required for oxygen evolution is 328mV, and the voltage required for full water dissolution is 1.847V.
Smart Images

Figure CN119506942A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials, relates to electrocatalytic materials, and specifically relates to a Ni3S2 / VN-C / C dual-functional electrocatalytic material and a preparation method and application thereof. Background Art
[0002] Chemical water splitting to produce hydrogen is a sustainable energy conversion and storage technology that can meet energy needs and alleviate carbon emissions caused by excessive consumption of fossil fuels. Water splitting involves two core processes: hydrogen evolution reaction (HER) at the cathode and oxygen evolution reaction (OER) at the anode. Unfortunately, OER and HER are plagued by their sluggish kinetics, which require state-of-the-art electrocatalysts (such as Ru-based or Ir-based for OER; and Pt-based for HER) to promote them [H. Qi, P. Zhang, H. Wang, Y. Cui, X. Liu, X. She, Y. Wen, T. Zhan, Cu2Se nanowires shelled with NiFe layered doublehydroxide nanosheets for overall water-splitting, J. Colloid Interface Sci. 599 (2021) 370–380]. However, the low earth reserves, high prices, and poor long-term stability of precious metals greatly limit their large-scale application. Many efforts have been made to develop non-precious metal electrocatalysts with high activity and durability for electrochemical water splitting. Reported electrocatalysts include transition metal sulfides, carbides, nitrides and phosphides for HER electrocatalysis, and transition metal (hydride) oxides for OER electrocatalysis. Among them, Ni3S2 with multiple valence states, strong chemical adsorption capacity for hydrogen, and metallic properties is the best choice for OER and HER electrocatalysts [Z.Mamiyev, et al., Metal Sulde Photocatalysts for Hydrogen Generation: A Review of Recent Advances, Catalysts, 2022, 12, 1–36.40]. However, its disadvantages such as low specific surface area and poor ion transport kinetics are relatively prominent, and the stability of nickel sulfide is relatively insufficient, which seriously hinders its further improvement.
[0003] Heterostructure engineering is an effective strategy to promote catalytic activity, drawing on improved electron transfer capabilities and tuned electronic structures. The interfaces inside heterostructures are believed to be the actual catalytic active sites. [S.Tao, G.Zhang, B.Qian, J.Yang, S.Chu, C.Sun, D.Wu, W.Chu, L.Song, Appl.Catal.B:Environ.2023,330,122600.
[12] Q.Wen, K.Yang, D.Huang, G.Cheng, X.Ai, Y.Liu, J.Fang, H.Li, L.Yu, T.Zhai, Adv.Energy Mater.2021,11,2102353] Designing heterostructures and combining two or more heterogeneous materials to achieve complementary advantages and improve structural properties is considered to be an effective method to improve catalytic activity [Z.Li, M.Hu, P.Wang, J.Liu, J.Yao, C.Li, Corrd.Chem.Rev.2021,439,213953].
[0004] Existing heterogeneous electrocatalysts still have defects such as limited stability, easy poisoning and deactivation after long-term use, special requirements for pH, temperature or electrolyte concentration, and limited application range. It is worth noting that HER electrocatalysts perform well in acidic electrolytes, while OER electrocatalysts work better under alkaline conditions. The pH mismatch between OER and HER composite electrocatalysts will inevitably lead to poor water splitting performance. Although HER and OER bifunctional electrocatalysts have been developed to simplify water splitting systems and reduce costs, they usually show excellent HER activity and relatively poor OER catalytic activity, and vice versa [T. Zhan, X. Liu, S. Lu, W. Hou, Nitrogen doped NiFe layered double hydroxide / reduced graphene oxide mesoporous nanosphere as an effective bifunctional electrocatalyst for oxygen reduction and evolution reactions, Appl. Catal. B Environ. 205 (2017) 551–558]. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a Ni3S2 / VN-C / C bifunctional electrocatalytic material with good morphology, good electrocatalytic performance and long-term stability in a strong alkaline environment, as well as a preparation method and application thereof. The preparation method is simple and the product morphology is controllable.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a Ni3S2 / VN-C / C bifunctional electrocatalytic material comprises the following steps:
[0008] Step 1: taking a nickel source and a vanadium source at a molar ratio of (0.5-3) to a vanadium source, and taking thioacetamide at a molar ratio of (1-2) to a sulfur source, mixing and grinding the above raw materials evenly, adding them to ethanol, stirring on a magnetic stirrer to dissolve them, and obtaining a mixed solution;
[0009] Step 2, transfer the mixed solution prepared in step 1 to the polytetrafluoroethylene liner of the autoclave, put the pretreated C / C composite material into it, ensure that it is immersed in the mixed solution, seal it well, and finally place the autoclave in an electric blast drying oven, set the temperature parameter to 100-170°C, and keep it for 10-16h for solvent thermal reaction. After the invention is completed and cooled to room temperature, take it out, wash it, seal it and dry it at room temperature to obtain V-Ni3S2-C / C;
[0010] Step 3: Place the V-Ni3S2-C / C obtained in step 2 in a porcelain boat, place the small porcelain boat at one end of the large porcelain boat, place a nitrogen source at the other end to ensure that the molar ratio of the V source to the nitrogen source is 1:(4-6), place the nitrogen source at the air inlet end, and use a tubular furnace to raise the temperature from room temperature to 700-1200°C in an argon atmosphere and calcine for 1-4 hours to obtain Ni / Ni3S2 / VN-C / C.
[0011] The present invention also has the following technical features:
[0012] Preferably, the nickel source in step 1 includes any one of nickel dichloride, nickel acetylacetonate and nickel nitrate.
[0013] Preferably, the vanadium source in step 1 includes any one of vanadium trichloride, vanadium acetylacetonate and vanadium sulfate.
[0014] Preferably, the pretreatment method of the C / C composite material described in step 2 includes: using ultrapure water and ethanol to alternately perform ultrasonic cleaning on the carbon / carbon matrix, each time for 10 minutes, repeated 3 times, and finally placing it in a culture dish and drying it at 50°C in an electric blast drying oven for 6 hours.
[0015] Preferably, the filling ratio of the polytetrafluoroethylene liner in step 2 is 50%.
[0016] Preferably, the washing in step 2 is performed by alternately rinsing with ultrapure water and ethanol for 3 to 5 times.
[0017] Preferably, the nitrogen source in step three includes any one of urea, dicyandiamide and melamine.
[0018] Preferably, the heating rate of the tubular furnace during the calcination process in step three is 10° C. / min.
[0019] The present invention also protects a Ni3S2 / VN-C / C bifunctional electrocatalytic material prepared by the method as described above and its application as an electrocatalyst for electrolysis of water to produce hydrogen, electrolysis of water to produce oxygen or full water splitting in a strong alkaline environment.
[0020] Compared with the prior art, the present invention has the following technical effects:
[0021] The present invention grows uniformly distributed nanotube-shaped Ni / Ni3S2 and nanoparticle-shaped VN on a carbon / carbon matrix through a simple two-step method to obtain a Ni3S2 / VN-C / C bifunctional electrocatalytic material with many exposed active sites and a large specific surface area. The heterogeneous interface formed by Ni3S2 and VN can adjust the redistribution of charges to obtain the adsorption free energy of a suitable intermediate, thereby fast ion transmission and improved catalytic rate; the use of a C / C self-supporting substrate not only provides more active sites, but also its excellent conductivity facilitates the rapid transmission of electrons on the catalyst surface, and its excellent mechanical stability ensures the stability of the catalyst during the reaction process; the material has an overpotential of only 165mV for electrocatalytic hydrogen evolution (HER) and only 328mV for electrocatalytic oxygen evolution (OER) at a current density of 100 in an alkaline solution, and the voltage required for complete water splitting is 1.847V;
[0022] The present invention prepares a Ni3S2 and VN composite electrocatalyst on a carbon / carbon conductive substrate by hydrothermal and sintering methods, adopts an ammonia-free and nitrogen-free atmosphere, has a simple process, a controllable process, is green and safe, and has a good product morphology. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 XRD pattern of Ni / Ni3S2 / VN-C / C prepared in Example 1;
[0024] Figure 2 This is a SEM photo of Ni / Ni3S2 / VN-C / C prepared in Example 1;
[0025] Figure 3 The LSV curve of electrocatalytic hydrogen evolution of Ni / Ni3S2 / VN-C / C prepared in Example 1;
[0026] Figure 4 The LSV curve of electrocatalytic oxygen evolution of Ni / Ni3S2 / VN-C / C prepared in Example 1;
[0027] Figure 5 This is the LSV curve of the electrocatalytic water splitting of Ni / Ni3S2 / VN-C / C prepared in Example 1. DETAILED DESCRIPTION
[0028] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0029] Embodiment 1:
[0030] Step 1: weigh 206.15 mg of nickel dichloride hexahydrate (NiCl2·6H2O) and 125.84 mg of vanadium trichloride (VCl3), with the molar ratio of nickel to vanadium source being 1:1; weigh 60 mg of thioacetamide, with the molar ratio of nickel to S source being 1:1; mix and grind the above raw materials evenly, add them into 25 mL of ethanol, stir on a magnetic stirrer for 30 min to dissolve them, and obtain a mixed solution;
[0031] Step 2: Ultrapure water and ethanol are used to perform ultrasonic cleaning on the carbon / carbon substrate alternately, each time for 10 minutes, repeated 3 times, and finally placed in a culture dish, and dried in an electric blast drying oven at 50° C. for 6 hours for standby use;
[0032] The mixed solution prepared in step 1 is transferred to a 50 mL polytetrafluoroethylene-lined autoclave, and a piece of treated C / C composite material is placed to ensure that it is immersed in the solution, and the autoclave is sealed to keep the volume filling ratio controlled at 50%. Finally, the autoclave is placed in an electric blast drying oven, and the temperature parameters are set to 120°C and the insulation time is 10h. After the invention is completed and cooled to room temperature, the V-Ni3S2-C / C is taken out, and it is rinsed alternately with ultrapure water and ethanol for 3 times, and then sealed and dried at room temperature;
[0033] Step 3: Place the V-Ni3S2-C / C obtained in step 2 in a porcelain boat, place the small porcelain boat at one end of the large porcelain boat, and place a nitrogen source, i.e. 334 mg of dicyandiamide, at the other end. The molar ratio of the V source to the nitrogen source is 1:5. Place the nitrogen source at the air inlet end, and use a tubular furnace to calcine for 2 hours in an argon atmosphere. The calcination temperature is 800°C, and the heating rate is 10°C / min to obtain a Ni / Ni3S2 / VN-C / C sample.
[0034] Figure 1 The SEM photo of Ni / Ni3S2 / VN-C / C prepared in Example 1; Figure 1 It can be seen that nanotube-shaped Ni / Ni3S2 and nanoparticle-shaped VN are grown on the carbon / carbon matrix, and their distribution is uniform and their specific surface area is large.
[0035] Figure 2 The XRD pattern of Ni / Ni3S2 / VN-C / C prepared in Example 1; Figure 2 As shown, the C peak at 26.3° is attributed to the matrix; the peaks at 44.5°, 51.8°, and 76.3° are attributed to the (111), (200), and (220) crystal planes of Ni (JCPDS card number 89-7128); the peaks at 21.76°, 31.101°, 37.795°, 44.349°, 50.112°, and 55.155° are attributed to the (1 0 0), (-1 1 0), (1 1 1), (2 0 0), (2 -1 0), and (2 -1 0) crystal planes of Ni3S2 (JCPDS card number 85-1802). 1) Crystal planes; the peaks at 37.7°, 43.8°, 63.7°, and 76.5° are attributed to the (111), (200), (220), and (311) crystal planes of VN (JCPDS card number 35-0768).
[0036] In a standard three-electrode system, the electrocatalytic test of Ni / Ni3S2 / VN-C / C was carried out in 1M KOH electrolyte solution, such as Figure 3 To evaluate the electrocatalytic hydrogen evolution performance of the prepared samples, the -1 For linear sweep voltammetry (LSV) tests, overpotentials of 165, 389, and 521 mV were required at current densities of 100, 500, and 1000, respectively. Figure 4 In order to evaluate the electrocatalytic oxygen evolution performance of the prepared samples, the -1 Linear sweep voltammetry (LSV) tests showed that electrocatalytic hydrogen evolution required overpotentials of 328, 435, and 543 mV at current densities of 100, 500, and 1000, respectively. Figure 5 Similarly, in order to evaluate the electrocatalytic water splitting performance of the prepared samples, the -1 Linear sweep voltammetry (LSV) tests were performed, and only a voltage of 1.847 V was required for complete water splitting at a current density of 100.
[0037] Example 2
[0038] Step 1, weigh 206.15 mg of nickel dichloride hexahydrate (NiCl2·6H2O), weigh 125.84 mg of vanadium trichloride (VCl3), the molar ratio of nickel to vanadium source is 1:1, weigh 120 mg of thioacetamide, and ensure that the molar ratio of nickel to S source is 1:2; mix and grind the above raw materials evenly, add them to 25 mL of ethanol, stir on a magnetic stirrer for 30 minutes to dissolve them, and obtain a mixed solution;
[0039] Step 2: Ultrapure water and ethanol are used to perform ultrasonic cleaning on the carbon / carbon substrate alternately, each time for 10 minutes, repeated 3 times, and finally placed in a culture dish, and dried in an electric blast drying oven at 50° C. for 6 hours for standby use;
[0040] The mixed solution prepared in step 1 is transferred to a 50 mL polytetrafluoroethylene-lined autoclave, and a piece of treated C / C composite material is placed to ensure that it is immersed in the solution, and the autoclave is sealed to keep the volume filling ratio controlled at 50%; finally, the autoclave is placed in an electric blast drying oven, the temperature parameter is set to 120°C, and the insulation time is 10h. After the invention is completed and cooled to room temperature, the V-Ni3S2-C / C is taken out, and it is rinsed 4 times alternately with ultrapure water and ethanol, and then sealed and dried at room temperature;
[0041] Step 3: Place the V-Ni3S2-C / C obtained in step 2 in a porcelain boat, place the small porcelain boat at one end of the large porcelain boat, and place a nitrogen source, i.e. 334 mg of dicyandiamide, at the other end, to ensure that the molar ratio of the V source to the nitrogen source is 1:5, place the nitrogen source at the air inlet end, and use a tubular furnace to calcine for 2 hours in an argon atmosphere at a calcination temperature of 800°C and a heating rate of 10°C / min to obtain a Ni / Ni3S2 / VN-C / C sample.
[0042] Embodiment 3:
[0043] Step 1, weigh 256.91 mg of nickel acetylacetonate (Ni(CH3COCHCOCH3)2, weigh 314.6 mg of vanadium trichloride (VCl3), ensure that the molar ratio of nickel to vanadium source is 1:2, weigh 112.5 mg of thioacetamide, ensure that the molar ratio of nickel to S source is 2:3; mix and grind the above raw materials evenly, add them into 25 mL of ethanol, stir on a magnetic stirrer for 30 min to dissolve them, and obtain a mixed solution;
[0044] Step 2: Ultrapure water and ethanol are used to perform ultrasonic cleaning on the carbon / carbon substrate alternately, each time for 10 minutes, repeated 3 times, and finally placed in a culture dish, and dried in an electric blast drying oven at 50° C. for 6 hours for standby use;
[0045] The stirred solution was transferred to a 50 mL polytetrafluoroethylene-lined autoclave, and a piece of treated C / C composite material was placed to ensure that it was immersed in the solution, and the autoclave was sealed to keep the volume filling ratio controlled at 50%. Finally, the autoclave was placed in an electric blast drying oven, and the temperature parameters were set to 140°C and the insulation time was 16h. After the invention was completed and cooled to room temperature, the V-Ni3S2-C / C was taken out, and ultrapure water and ethanol were used to rinse alternately for 5 times, and then sealed and dried at room temperature;
[0046] Step 3. Place the V-Ni3S2-C / C obtained in step 2 in a porcelain boat, place the small porcelain boat at one end of the large porcelain boat, and place a nitrogen source, i.e., 1513.4 mg of melamine, at the other end, to ensure that the molar ratio of the V source to the nitrogen source is 1:6. Place the nitrogen source at the air inlet end, and use a tubular furnace to calcine for 2 hours in an argon atmosphere at a calcination temperature of 800°C and a heating rate of 10°C / min to obtain a Ni / Ni3S2 / VN-C / C sample.
[0047] Embodiment 4:
[0048] Step 1, weigh 290.79 mg nickel nitrate, weigh 174.13 mg vanadium acetylacetonate, ensure that the molar ratio of nickel to vanadium source is 2:1, weigh 112.5 mg thioacetamide, ensure that the molar ratio of nickel to S source is 2:3; mix and grind the above raw materials evenly, add them to 25 mL of ethanol, stir on a magnetic stirrer for 30 min to dissolve them, and obtain a mixed solution;
[0049] Step 2: Ultrapure water and ethanol are used to perform ultrasonic cleaning on the carbon / carbon substrate alternately, each time for 10 minutes, repeated 3 times, and finally placed in a culture dish, and dried in an electric blast drying oven at 50° C. for 6 hours for standby use;
[0050] The stirred solution was transferred to a 50 mL polytetrafluoroethylene-lined autoclave, and a piece of treated C / C composite material was placed to ensure that it was immersed in the solution, and the autoclave was sealed to keep the volume filling ratio controlled at 50%. Finally, the autoclave was placed in an electric blast drying oven, and the temperature parameter was set to 100° C. The insulation time was 15 h. After the invention was completed and cooled to room temperature, the V-Ni3S2-C / C was taken out, and ultrapure water and ethanol were used to rinse alternately for 5 times, and the autoclave was sealed and dried at room temperature;
[0051] Step 3: Place the V-Ni3S2-C / C obtained in step 2 in a porcelain boat, place the small porcelain boat at one end of the large porcelain boat, and place a nitrogen source, i.e., 120.1 mg of urea, at the other end to ensure that the molar ratio of the V source to the nitrogen source is 1:4. Place the nitrogen source at the air inlet end, and use a tubular furnace to calcine for 4 hours in an argon atmosphere at a calcination temperature of 700°C and a heating rate of 10°C / min to obtain a Ni / Ni3S2 / VN-C / C sample.
[0052] Embodiment 5:
[0053] Step 1, weigh 256.91 mg of nickel acetylacetonate (Ni(CH3COCHCOCH3)2, weigh 91 mg of vanadium sulfate (VSO4·7H2O), ensure that the molar ratio of nickel to vanadium source is 3:1, weigh 112.5 mg of thioacetamide, ensure that the molar ratio of nickel to S source is 2:3; mix and grind the above raw materials evenly, add them into 25 mL of ethanol, stir on a magnetic stirrer for 30 min to dissolve them, and obtain a mixed solution;
[0054] Step 2: Ultrapure water and ethanol are used to perform ultrasonic cleaning on the carbon / carbon substrate alternately, each time for 10 minutes, repeated 3 times, and finally placed in a culture dish, and dried in an electric blast drying oven at 50° C. for 6 hours for standby use;
[0055] The stirred solution was transferred to a 50 mL polytetrafluoroethylene-lined autoclave, and a piece of treated C / C composite material was placed to ensure that it was immersed in the solution, and the autoclave was sealed to keep the volume filling ratio controlled at 50%. Finally, the autoclave was placed in an electric blast drying oven, and the temperature parameters were set to 170°C and the insulation time was 12h. After the invention was completed and cooled to room temperature, the V-Ni3S2-C / C was taken out, and ultrapure water and ethanol were used to rinse alternately for 5 times, and then sealed and dried at room temperature;
[0056] Step 3. Place the V-Ni3S2-C / C obtained in step 2 in a porcelain boat, place the small porcelain boat at one end of the large porcelain boat, and place a nitrogen source, i.e., 252.24 mg of melamine, at the other end, to ensure that the molar ratio of the V source to the nitrogen source is 1:6. Place the nitrogen source at the air inlet end, and use a tubular furnace to calcine for 1 hour in an argon atmosphere. The calcination temperature is 1200°C, and the heating rate is 10°C / min to obtain a Ni / Ni3S2 / VN-C / C sample.
[0057] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a Ni3S2 / VN-C / C bifunctional electrocatalytic material, characterized in that: The following steps are involved: Step 1: taking a nickel source and a vanadium source at a molar ratio of (0.5-3) to a vanadium source, and taking thioacetamide at a molar ratio of (1-2) to a sulfur source, mixing and grinding the above raw materials evenly, adding them to ethanol, stirring on a magnetic stirrer to dissolve them, and obtaining a mixed solution; Step 2, transfer the mixed solution prepared in step 1 to the polytetrafluoroethylene liner of the autoclave, put the pretreated C / C composite material into it, ensure that it is immersed in the mixed solution, seal it well, and finally place the autoclave in an electric blast drying oven, set the temperature parameter to 100-170°C, and keep it for 10-16h for solvent thermal reaction. After the invention is completed and cooled to room temperature, take it out, wash it, seal it and dry it at room temperature to obtain V-Ni3S2-C / C; Step 3: Place the V-Ni3S2-C / C obtained in step 2 in a small porcelain boat, place the small porcelain boat at one end of a large porcelain boat, place a nitrogen source at the other end to ensure that the molar ratio of the vanadium source to the nitrogen source is 1:(4-6), place the nitrogen source at the air inlet end, use a tubular furnace to raise the temperature from room temperature to 700-1200°C in an argon atmosphere, and calcine for 1-4 hours to obtain Ni / Ni3S2 / VN-C / C.
2. The method for preparing the Ni3S2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The nickel source described in step 1 includes any one of nickel dichloride, nickel acetylacetonate and nickel nitrate.
3. The method for preparing the Ni3S2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The vanadium source described in step 1 includes any one of vanadium trichloride, vanadium acetylacetonate and vanadium sulfate.
4. The method for preparing the Ni3S2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The pretreatment method of the C / C composite material described in step 2 includes: using ultrapure water and ethanol to ultrasonically clean the carbon / carbon matrix alternately, each time for 10 minutes, repeated 3 times, and finally placing it in a culture dish and drying it in an electric blast drying oven at 50°C for 6 hours.
5. The method for preparing the Ni3S2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The filling ratio of the polytetrafluoroethylene liner described in step 2 is 50%.
6. The method for preparing the Ni3S2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The washing described in step 2 is to use ultrapure water and ethanol to rinse alternately 3 to 5 times.
7. The method for preparing the Ni3S2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The nitrogen source described in step three includes any one of urea, dicyandiamide and melamine.
8. The method for preparing the Ni3S2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The heating rate of the tubular furnace during the calcination process described in step 3 is 10°C / min.
9. A Ni3S2 / VN-C / C bifunctional electrocatalytic material prepared by the method according to any one of claims 1 to 8.
10. Use of the Ni3S2 / VN-C / C bifunctional electrocatalytic material as claimed in claim 9 as an electrocatalyst for producing hydrogen or oxygen by electrolysis of water or for overall water splitting in a strong alkaline environment.
Citation Information
Patent Citations
Synthesis method of vanadium-modified Ni3S2 electrocatalyst automatically assembled from rodlike shape into ball-flower shape
CN108325539A
Preparation method and electrocatalytic nitrogen reduction application of ultrathin nanosheet vanadium-doped nickel sulfide nanopowder
CN110124694A
High-efficiency wide-pH self-supporting Cu3P / VN-C / C electro-catalytic material as well as preparation method and application thereof
CN117845233A